Gross-Neveu model with O (2)L× O (2)R chiral symmetry: Duality with Zakharov-Mikhailov model and large N solution - Thies, Michael (Physical Review D, 2023)
The two-flavor Gross-Neveu model with U(2)L×U(2)R chiral symmetry in 1+1 dimensions is used to construct a novel variant of four-fermion theories with O(2)L×O(2)R chiral symmetry. The spontaneous breaking of the group O(2), a continuous group with two connected components (rotations and reflections), gives rise to new phenomena. It is ideally suited to describe a situation where two distinct kinds of condensation compete, in particular chiral symmetry breaking (particle-hole condensation) and Cooper pairing (particle-particle condensation). After solving the O(2) chiral Gross-Neveu model in detail, we demonstrate that it is dual to another classically integrable model due to Zakharov and Mikhailov. The duality enables us to solve the quantum version of this model in the large N limit with semiclassical methods, supporting its integrability at the quantum level. The resulting model is the unique four-fermion theory sharing the full Pauli-Gürsey symmetry with free, massless fermions ("perfect Gross-Neveu model") and provides us with a solvable model for competing chiral and Cooper pair condensates, including explicit soliton dynamics and the phase diagram.
CRIS-Team Scopus Importer:2023-05-26